Renal Sympathetic Denervation Attenuates Congestive Heart Failure in Angiotensin II-Dependent Hypertension: Studies with Ren-2 Transgenic Hypertensive Rats with Aortocaval Fistula - Zuzana Honetschlagerová; Olga Gawrys; Šárka Jíchová; Petra Škaroupková; Soňa Kikerlová; Zdeňka Vaňourková; Zuzana Husková; Vojtěch Melenovský; Elzbieta Kompanowska-Jezierska; Janusz Sadowski; František Kolář; Jiří Novotný; et al. (Karger Publishers, 2021)
Objective: We examined if renal denervation (RDN) attenuates the progression of aortocaval fistula (ACF)-induced heart failure or improves renal hemodynamics in Ren-2 transgenic rats (TGR), a model of angiotensin II (ANG II)-dependent hypertension. Methods: Bilateral RDN was performed 1 week after creation of ACF. The animals studied were ACF TGR and sham-operated controls, and both groups were subjected to RDN or sham denervation. In separate groups, renal artery blood flow (RBF) responses were determined to intrarenal ANG II (2 and 8 ng), norepinephrine (NE) (20 and 40 ng) and acetylcholine (Ach) (10 and 40 ng) 3 weeks after ACF creation. Results: In nondenervated ACF TGR, the final survival rate was 10 versus 50% in RDN rats. RBF was significantly lower in ACF TGR than in sham-operated TGR (6.2 ± 0.3 vs. 9.7 ± 0.5 mL min−1 g−1, p < 0.05), the levels unaffected by RDN. Both doses of ANG II decreased RBF more in ACF TGR than in sham-operated TGR (−19 ± 3 vs. −9 ± 2% and −47 ± 3 vs. −22 ± 2%, p < 0.05 in both cases). RDN did not alter RBF responses to the lower dose, but increased it to the higher dose of ANG II in sham-operated as well as in ACF TGR. NE comparably decreased RBF in ACF TGR and sham-operated TGR, and RDN increased RBF responsiveness. Intrarenal Ach increased RBF significantly more in ACF TGR than in sham-operated TGR (29 ± 3 vs. 17 ± 3%, p < 0.05), the changes unaffected by RDN. ACF creation induced marked bilateral cardiac hypertrophy and lung congestion, both attenuated by RDN. In sham-operated but not in ACF TGR, RDN significantly decreased mean arterial pressure. Conclusion: The results show that RDN significantly improved survival rate in ACF TGR; however, this beneficial effect was not associated with improvement of reduced RBF or with attenuation of exaggerated renal vascular responsiveness to ANG II.